Analysis of Risk Management Improvement of Tapioca Flour Product in The Supply Chain Using The House of Risk Method - Dewi, Irma Nurmala; Putra, Arta Rusidarma; Sukmawati, Sri; Desriyati, Welly (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2022)
When present in a supply chain activity process, there are many different risks that can disrupt the supply chain flow to the point where it cannot operate effectively. As a result, it is necessary to improve supply chain performance in stages and be carried out continuously (sustainably). It is essential to reduce and get around the various risks. This study aimed to mitigate risks in the supply chain activities of tapioca flour products at PT Starch Solution International, Tbk Karawang, West Java, which identified possible risks that may arise in the tapioca flour supply chain. The method used in this study is the Failure Mode and Effect Analysis and Quality Function Deployment methods developed to identify and evaluate problems. The Supply Chain Operation Reference dimensions use to determine the business process criteria. Following the completion of the research, Incorporated The finding into the development of potential risk values. These values then establish the priority of risk agents to be mitigated using the House of Risk methodology. The outputs of House of Risk one (1) Utilize as inputs for the subsequent stage of the process. House of Risk two (2) is a framework for risk reduction strategies applicable to various risk sources (risk agents). According to the findings of the research conducted and the calculations performed by House of Risk two (2), eight risk reduction strategies should implement as quickly as possible. The highest priority is determining proper storage conditions in raw material warehouses, strengthening and standardizing invoice-making agreements with suppliers, and being more selective in choosing raw materials suppliers. It reminds suppliers to prioritize the soil suitable for planting, cassava quality standards according to needs, carrying out work and operational routes, and scheduling.